Le fratture periprotesiche: scelta della sintesi nell’anca - Manca, M.; Sirianni, R.; Isola, A.; Giachetti, G.; Caggiari, G.; D’Arcangelo, M.; Iacopinelli, M. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC FRACTURES: CHOOSING THE CORRECT HIP TREATMENT Periprosthetic fractures are constantly increasing. The key to a correct treatment lies in an appropriate classification, preoperative planning and in different surgical options. The management of these fractures is rather demanding, as the surgeon has to face simultaneously a loose implant, poor bone quality or bone loss, in a frail, elderly patient. We suggest an algorithm for the treatment of periprosthetic fractures of femur, acetabulum and pelvis, and for interprosthetic fractures.